FLORES GALINDI, Alberto. Aristocracia y plebe; Lima, 1760-1830 Mosca Azul Editores. Lima. ! 9g4_ 272 págs. (notas. cuadros. anexo y bibliografía). - Iwasaki Cauti, Fernando (Histórica, 1986)
No contiene resumen